2011
DOI: 10.1002/adsc.201100173
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Nucleophilic Addition to Aldehydes with Polar α‐ and α,β‐Substituents

Abstract: Abstract:The stereoselectivities obtained in Lewis acid-promoted Mukaiyama aldol additions and Sakurai allylations of mono-, and syn-and anti-disubstituted aldehydes possessing various polar a-and bsubstituents under non-chelating conditions are presented. The stereochemical outcome in the nucleophilic addition to a-substituted aldehydes containing an a-benzyloxy, a-fluoro or a-sulfonamide substituent are accurately predicted by current stereoinduction models.In contrast, the selectivitites obtained from addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…The absolute configuration of the product was assigned by analogy to S3. The (2S,3S) enantiomer was prepared according to the general procedure using (S,R)-13 (20 mol %) from (Z)-5phenylpent-2-en-1-ol (12). From a 1.0 mmol (162 mg) scale bromochlorination employing (S,R)-13 (86 mg, 0.2 mmol) was isolated product (−)-S18 in 92% yield (255 mg) of 91% ee as a >20:1 mixture of constitutional isomers after purification by flash column chromatography (25 g silica gel, 5 to 20% ethyl acetate/hexanes gradient).…”
Section: S18mentioning
confidence: 99%
“…The absolute configuration of the product was assigned by analogy to S3. The (2S,3S) enantiomer was prepared according to the general procedure using (S,R)-13 (20 mol %) from (Z)-5phenylpent-2-en-1-ol (12). From a 1.0 mmol (162 mg) scale bromochlorination employing (S,R)-13 (86 mg, 0.2 mmol) was isolated product (−)-S18 in 92% yield (255 mg) of 91% ee as a >20:1 mixture of constitutional isomers after purification by flash column chromatography (25 g silica gel, 5 to 20% ethyl acetate/hexanes gradient).…”
Section: S18mentioning
confidence: 99%
“…Somfai and coworkers have disclosed interesting studies to elucidate the origin of reversed diastereoselectivity of Mukaiyama aldol additions to α-silyloxy and chloro aldehydes. 11 En route to developing methods for the in situ generation of ( Z )-vinylzinc reagents, our group observed unexpected chelation-controlled additions to β-silyloxy aldehydes in the presence of ZnBr 2 , albeit in modest selectivity (Scheme 1b). 12 In efforts toward the synthesis of mycolactone polyketides, Burkart observed high selectivity for the chelation-controlled product in the allylation of aldehyde ent- 1 using allyltrichlorostannane (Scheme 1c).…”
mentioning
confidence: 99%
“…and found that aldehydes with fluoro‐ and oxygen containing substituents were under Cornforth control, but that nitrogen containing substituents could be under Felkin–Anh or Cornforth control, depending on the circumstances. In the Mukaiyama aldol additions to chloro‐substituted aldehydes, Somfai et al reported a change in mechanism from Cornforth to anti‐Cornforth as the nucleophile gets larger …”
Section: Introductionmentioning
confidence: 99%
“…In the Mukaiyama aldol additions to chlorosubstituted aldehydes, Somfai et al reported a change in mechanism from Cornforth to anti-Cornforth as the nucleophile gets larger. [13] In this work, the goal is to examine the electronic effects of diastereoselective addition to alpha substituted polar ketones using hydride nucleophiles. In comparison with the boron enolate and aldol reactions mentioned above, hydride nucleophiles are less sterically demanding and thus serve as more sensitive mechanistic probes of electronic effects.…”
Section: Introductionmentioning
confidence: 99%